KOMPETENSI PROFESIONAL GURU IPS DI SMP NEGERI SE-KOTA SAMPIT - M. Qahfi; Novianti Rahmawati; Risa Ramadhani (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2019)
Teacher professional competence is related to the task of a teacher in teaching. This study was conducted to determine the Professional Competencies of Social Sciences Subjects in Public Middle Schools in Sampit City. The subjects in this study were all 28 teachers who taught Social Sciences at the State Middle School in Sampit City. The data collection technique used was the questionnaire method (questionnaire). Based on the Quantitative Descriptive analysis and calculation through the Microsoft Excel 2007 program Teacher Professional Competence in Social Studies Subjects in State Middle Schools in Sampit City 2018/2019 Academic Year was in the enough category of 67,86%